Klondikers crossing frozen Lake Laberge with boats and sleds outfitted with sails, Yukon Territory, 1897. - La Roche, Frank (1897)
Caption on image: ""Ice-sailing across Lake Le Barge"" ""Ice sailing across Lake Le Barge. The lake is a beautiful sheet of water thirty-five miles long. It is about twenty-four miles from the White Horse Rapids and the intervening River is smooth and deep the whole distance. It is no uncommon thing for the boat to be wind bound for several days at a time. When winter has set in and the lake has become a sheet of ice, the delightful sensation of sailing across the frozen surface will not only be enjoyed but will hasten the traveler on his northward journey. It is exhilarating and heathful, and if the wind be favorable it will recompense the gold-seeker for previous delays. The group in the photograph presents the appearance of a pleasure party rather than men who are fighting hardships."" (Frank La Roche, En Route to the Klondike, 1898) Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number